Metabolic syndrome may be associated with a lower prevalence of iron deficiency in Ecuadorian women of reproductive age (2021)
ABSTRACT: The present study aimed to assess the associations of the stages of Fe deficiency (Fe deficiency without anaemia (ID) and Fe-deficiency anaemia (IDA)) and anaemia with metabolic syndrome (MetS) in Ecuadorian women. A cross-sectional study was conducted in 5894 women aged 20–59 years, based on data from the 2012 Ecuadorian National Health and Nutrition Survey. The sample was stratified by age. A χ2 test was used to assess the possible associations of ID, IDA and anaemia with MetS. The prevalence ratio (PR) for each stage of Fe deficiency and anaemia was estimated considering women without MetS as a reference. The total prevalence of MetS, ID, IDA and anaemia was 32⋅3%(SE 0⋅6), 6⋅2%(SE 0⋅3), 7⋅1%(SE 0⋅3) and 5⋅0%(SE 0⋅3), respectively. In women aged 20–29, 30–39 and 40–49 years, MetS was associated with a lower prevalence of ID (PR (95 % CI; P-value)): 0⋅17 (0⋅06, 0⋅46; P < 0⋅001), 0⋅69 (0⋅48, 0⋅99; P = 0⋅044) and 0⋅44 (0⋅29, 0⋅67; P < 0⋅001), respectively. In women aged 50–59 years, MetS was associated with IDA and anaemia (PR (95 % CI; P-value)): 0⋅12 (0⋅02, 0⋅96; P = 0⋅026) and 0⋅22 (0⋅07, 0⋅64; P = 0⋅002), respectively. In conclusion, Ecuadorian women of reproductive age with MetS have a lower prevalence of ID compared with those without MetS. Furthermore, the MetS and IDA coexist at the population level. These findings require an analysis from a dietary pattern approach, which could provide key elements for developing public policies that simultaneously address all forms of malnutrition.